Prevalence of Shigella Serogroups and Their Antimicrobial Resistance Patterns in Southern Trinidad (Journal of Health, Population and Nutrition, 2009)
The serogroup distribution and antimicrobial susceptibility patterns of Shigella isolates obtained from stool specimens of persons with acute diarrhoea in community-based studies from southern Trinidad during 1997-2006 were reviewed. Of the 5,187 stool specimens, 392 (8%) were positive for Shigella organisms. From these 392 isolates, 88.8% were recovered from children aged >0-10 year(s). Shigella sonnei was the most frequently-isolated serogroup (75%), followed by S. flexneri (19%), S. boydii (4.1%), and S. dysenteriae (1.8%). S. flexneri was the major isolate among the >20-30 years age-group. The most common drug resistance among all age-groups was to ampicillin. All strains of S. flexneri, S. boydii, and S. dysenteriae were fully susceptible to aztreonam, gentamicin, and ciprofloxacin. S. sonnei, the most common species isolated, showed resistance to all antibiotics tested. The data showed that, throughout the study period, the resisÂtance to commonly-used drugs was relatively low. Since resistance to several drugs seems to be emerging, continuous monitoring of resistance patterns is mandatory for the appropriate selection of empiric antimiÂcrobial drugs in the therapy of suspected cases of shigellosis. Key words: Antibiotics; Community-based studies; Drug resistance, Microbial; Shigella; Dysentary, Bacillary; Trinidad and Tobago doi:10.3329/jhpn.v26i4.1889 J Health Popul Nutr 2008 Dec:26(4):456-462